Experimental and CFD analysis of copper plain and dimples tube at application of solar water heater. (2021) - Arun, M.; Barik, Debabrata; Sridhar, K.P.; Vignesh, G.
Abstract: Recently, solar-based technology in fuel film refining is applied to handle bitter water desalination in western China, and this research work has set the foundation for using the solar-oriented surface refining system. The objective of the solar water heater is to enhance the thermal performance throughout the flat plate collector tube on using a copper tube. Furthermore, to reduce the heat loss and to improve the heat transfer by modifying the geometric profile of the riser tube. To generate the turbulence flow throughout the riser tube to get a better heat transfer on the solar system. The modification of geometry is to create dimples inside the riser tube. The dimple is placing a circular type along the riser tube throughout its surface. To calculate the Nusselt number and pumping power at P/D different ratio. Finally, the experimental result is analysed with CFD analysis software, and the results are CFD compared with the experimental solar water heater.